Analisis Kesalahan Pemakaian Verba Bantu ~Tai dan ~Tagaru pada Mahasiswa Tingkat III Prodi Pendidikan Bahasa Jepang Universitas Riau - Afrinda, Sy. Afrinda; Widiati, Sri Wahyu Widiati Wahyu; Aibonotika, Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study is an analytical study of the auxiliary verb usage errors ~ tai and ~ tagaru. The purpose of this study was to determine the percentage error rate auxiliary verb usage ~tai and ~tagaru undertaken by third grade students Japanese Language Study Program Riau University academic year 2013/2014. Stages of the study include collecting process, identify, classify, explain, predict, and correct the mistakes the use of auxiliary verbs ~tai and ~tagaru in Japanese sentence.This research is quantitative descriptive method. This research was conducted in Japanese Language Study Program Teacher Training and Education Faculty of the University of Riau. Data in the form of a questionnaire consisting of 40 questions about being tested on 27 students. The total number of answers to 40 questions is 1080 answers. 40 questions are divided into 5 types of matter.The results showed that the percentage of errors made by third grade students Japanese Language Study Program University of Riau in answering the questionnaire items was 36.29%. The yield on each question is the type of question I amounted to 5.6%, type II amounted to 7.03%, type III amounted to 7.3%, about the type of IV amounted to 3.61%, and the type of matter V amounted to 12, 8%. Keywords: Error Analysis, ~tai, ~tagaru,